Sources of supplemental protein for cows wintered on milo stubble - McKee, M.; Kimple, K.; Conway, K. (Kansas State University. Agricultural Experiment Station, 2011)
We used 63 pregnant Hereford cows in mid gestation to evaluate need and source of supplemental protein on milo stubble. Cows fed free choice a 16% experimental nonprotein-nitrogen-based liquid supplement lost significantly more weight than cows receiving 2 lbs/head/day of a 16% natural protein cube or cows getting no protein supplement. Cows with access free choice to an 18% commercial nonprotein-nitrogen-based liquid supplement lost significantly more than cows receiving 2 lbs/head/day of 16% natural protein cube.
What's Ahead for Cattlemen? is known as Cattlemen’s Day, 1977
Keywords: Beef; Protein; Milo